PERUBAHAN BAHASA REMAJA DI YOUTUBE: ANALISIS SOSIOLINGUISTIK EPISODE NATASIA ADELINE BERTEMU COKI PARDEDE - Hanifa Qurrothul ‘Ain; Nurlailatul Qadri; Salwa Salsabila Lubis; Andika Putra Pratama; Muhammad Nabilaza Boyagain Kurniawan; Anggia Rahmawati; Ulfah Julianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the language changes used by teenagers on the YouTube social media platform in the episode “Warwan Binaan Melawan BBK” on the WKWK Project channel. The method used in this study is descriptive qualitative with a sociolinguistic approach. The collected data contains speech that includes slang terms, code combinations, and popular understandings spoken by the hosts and guests in the video. The data collection technique was carried out using the listening and note-taking method. The results of the study show 23 data on language changes that include English vocabulary, slang terms, and code combinations, such as “very real,” “cosplay,” “viral,” “update,” “challange,” “host,” “unjuk,” “on fire,” and “gas.” These language changes have informative, expressive, directive, and phatic functions. The use of these terms reflects the impact of social media, popular culture, and advances in digital technology on the language used by teenagers. The findings of this study indicate that teenagers’ language on social media is developing dynamically as a form of group identity, linguistic creativity, and an efficient means of communication in the digital environment.